The Influence of Human Resources on Village Economic Development Based on Bumdes in North Sumatra Regency Cities - Hairunnisah, Ade Isyana; Erlina, Erlina; Sirojuzilam, Sirojuzilam; Rujiman, Rujiman (International Conference on Sciences Development and Technology, 2022)
This research aims to analyze the influence of Human Resources (HR) on the development of the village economy based on Village-Owned Enterprises (Bumdes) in the Regency/City of North Sumatra. The research method used was a survey with a questionnaire as a data collection tool. The sample for this research consists of some Bumdes in North Sumatra. The results of the data analysis show that Human Resources (HR) has a significant influence on the development of the village economy through Bumdes in North Sumatra. Human resources who have adequate competence, knowledge, and skills can make a positive contribution to the management and growth of Bumdes, which in turn has an impact on improving the economy at the village level. The research results show that factors related to human resources, such as the level of education, training, and skills of Bumdes members, significantly influence the development of the village economy. A higher level of education and good training can increase the capacity and efficiency of Bumdes in managing various economic businesses at the village level. In addition, improved skills can help in business diversification and increase productivity. These findings have important implications for local governments, Bumdes, and village communities in efforts to improve village economic development. This research provides a deeper understanding of the role of human resources in supporting the development of the Bumdes-based village economy in North Sumatra. The results can become a basis for the government and related stakeholders to develop policies and programs that strengthen village human resources and support sustainable economic growth in this region. Investment is needed in human resource development through training, education, and skills development to support the growth of Bumdes and the village economy in North Sumatra.